Status of sea urchin resources in the east coast of Borneo - Siti Akmar Khadijah, Ab Rahim; Raymie, Nurhasan (Hindawi Publishing Corporation, 2016)
Sea urchins are marine benthos that live in different habitats available at shallow and deep waters. In Malaysia, Sabah is the only state that exploits sea urchins without knowing the status of natural stocks. This study identified the sea urchin species diversity at shallow subtidal zones in east coast of Borneo which is part of the Coral Triangle. Belt transects were deployed to quantify the species composition and qualitative observations on the habitat types were also noted. Simultaneously, documentation of species available in several wet markets was gathered through impromptu conversation with the sellers. In this study, a total of 10 species of sea urchin were recorded from 18 sampling sites, namely, Phyllacanthus imperialis, Diadema setosum, D. savignyi, Echinothrix calamaris, Mespilia globulus, Salmacis sphaeroides, Echinometra mathaei, Pseudoboletia maculata, Toxopneustes pileolus, and Tripneustes gratilla. The most dominant one that showed a wide distribution was D. setosum. Three species are new records for Malaysia. Among the study sites, Semporna district showed the highest species number. Our findings illustrate that shallow waters on the eastern part of Borneo support high diversity of sea urchin resources. Future study should explore the sea urchin diversity at deeper waters and also on the west coast of Sabah.